Optimization of Integrated Digital Marketing in The Marketing Strategy of MSME Culinary Tourism Centers (SWK) Wonorejo City of Surabaya - Iqbal Ramadhani Mukhlis; Robiah Al Adawiyah; Laely Aghe Africa; Diah Ekaningtyas; Arif Zeinfiki Djunaedy; Mellyza Silvy; Nur Rochmah (Journal of Applied Management and Business, 2023)
Micro, Small and Medium Enterprises (MSMEs) are an important sector in driving the Indonesian economy. The development and improvement of the MSME sector is also important to continue to strive for, one of which is through optimizing marketing strategies that are adapted to current technological and information developments. This study aims to analyze digital marketing strategies at SWK Wonorejo, Surabaya City. The research method used is descriptive qualitative with data triangulation approach. As for data collection techniques through interviews, observation, and documentation. The results showed that SWK Wonorejo combines segmentation analysis, targets and marketing mix design. In addition, an analysis of MSME sustainability and marketing implementation was carried out. MSME actors in SWK Wonorejo has marketed their products online through optimizing digital marketing media such as websites, Instagram, Google Business, and other media that can help market products effectively and efficiently.